Australia : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision, Insurance Regulation, Securities Regulation, and Payment Systems. (IMF Staff Country Reports; Country Report ;, 2006)
The Australian banking system, which holds approximately half of total financial systems assets, and is dominated by four major banks, is sound with high earnings, high asset growth, and low levels of problem assets. Stress tests did not reveal near-term stability concerns, suggesting the banking system is likely to be resilient to adverse shocks. Australia's financial supervisory structure of prudential authority and market conduct authority is sound overall. The medium-term challenges facing the banking sector are opportunities for growth and pressure on profitability.